Abiotic pathways for the formation of ozone-depleting and other trace gases in the polythermal glacier on Galindez Island, Maritime Antarctica - Bazylevska, M.; Bogillo, V. (Ukrainian Antarctic Journal, 2023)
The study aims to analyze trace gases in the composition of the polythermal glacier on Galindez Island in Maritime Antarctica (65°14’ S, 64°16’ W) and possible pathways for their abiotic formation in the snowpack and the superimposed or old cold ice. Polythermal glaciers are the most sensitive indicators of climate change. They are ideal for studying chemical post-depositional processes that alter the trace gas composition of the ice core air and the mechanisms involved under the current climate warming. This study is the first attempt to assess the concentration range of a large number of trace gases (except the previously studied O2, N2, Ar, and CO2) in polythermal and temperate glaciers, which are widespread in Greenland, Svalbard, Canadian Arctic, Alaska, Alps, Andes, Tibet, Altai, and Maritime Antarctica. The ice porosity varies from 0.6% to (unique to superimposed ice) 7%. Qualitative analysis by GC-MS was done for more than 200 organic and inorganic trace gases. A quantitative analysis of 27 compounds was performed along the vertical profile of the glacier, including CO2 and N2O, freons, chlorine-based solvents that are prohibited by the Montreal Protocol, F-, Cl-, Br- and I-containing halocarbons, COS, CS2, CH3SCH3, CH3SSCH3, and propene. Statistical data (mean, minimal, and maximum values) for ten horizontal levels of the glacier were calculated for their mixing ratios compared to background air. Most halocarbons, sulfur-containing compounds, and propene are characterized by high enrichment factors. This suggests that the species can be formed in the snowpack and firn of the glacier or its deep bubbling superimposed and old cold ice. Possible pathways of the gases formation include direct and indirect photochemical reactions of the triplet state dissolved organic matter (DOM) in snowpack without or in the presence of X– ions (X = Cl, Br, I), dark redox reactions of Fe3+, Mn4+, Cu2+, O3, H2O2 or radicals HOx (HOx = HO·,HO2·) with DOM in the presence of X–, reactions of HOX with DOM (with the participation of HOx, H2O2 or O3), free radical reactions with alkenes, alkynes, and alkyl radicals, and miscellaneous reactions of methylmethionine and/or S-containing peptides.